Ectogenesis, gender roles and beyond: looking through the lense of Islamic discourse - Mohammed Rizwan; Alvi, Ayesha (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ectogenesis, the development of embryos in artificial wombs, holds transformative potential in reproductive technology, challenging traditional gender roles and biological functions which calls for developing bioethical discourse beyond conventional deontological ethical frameworks. This paper is a synthesis review. It explores the implications of ectogenesis through an Islamic perspective, focusing on its impact on the family system and the role of women. It examines how this technology intersects with and potentially redefines gender dynamics within both secular and Islamic frameworks. By decoupling childbirth from the female body, ectogenesis prompts a re-evaluation of conventional gender roles and societal responsibilities historically assigned to women. Using Islamic theological texts, al-Quran, and Hadith, the study investigates concepts such as extracorporeal gestation, purposes of marriage, and gender roles to understand their alignment or conflict with ectogenesis. This research contributes to the dialogue on how cutting-edge and disruptive reproductive technologies necessitate evolving faith-based bioethical frameworks.